A new A-site excessive strategy to improve performance of layered perovskite cathode for intermediate-temperature solid oxide fuel cells. (20th March 2017) - Yang, Yang; Chen, Yonghong; Tian, Dong; Lu, Xiaoyong; Ding, Yanzhi; Yu, Weili; Lin, Bin
Highlights: A new A-site excessive strategy is reported to improve performance of layered perovskite cathode for IT-SOFCs. A new A-site excessive Gd1.05 Ba1.05 Co2 O5+δ layered perovskite was investigated as cathode materials for IT-SOFCs. A-site excess remarkably improves the electrical conductivity owing to the higher concentration of electron hole. A-site excess dramatically enhances the electrochemical performance at intermediate temperatures. Maximum power density of 830 mW cm −2 for YSZ-based IT-SOFC is obtained at 800 °C. Abstract: A new A-site excessive strategy is reported to improve performance of layered perovskite cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). A new A-site excessive Gd1+x Ba1+x Co2 O5+δ layered perovskite is investigated as cathode materials for IT-SOFCs. With an excess of A-site content, the crystal lattice and the thermal expansion coefficient increase slightly. The oxygen nonstoichiometry (δ) increases, while the oxygen vacancy decreases by defect chemistry analysis. A-site excessive Gd1.05 Ba1.05 Co2 O5+δ (GBC1.05) is well compatible with Gd0.2 Ce0.8 O2-δ at 1000 °C for 10 h. The electrical conductivity of GBC1.05 increases dramatically owing to the higher concentration of electron hole and the lower oxygen vacancy concentration. The electrochemical performance towards oxygen reduction reaction can be enhanced from 0.246 Ω cm 2 to 0.146 Ω cm 2 by introducing A-site excessive content of Gd and Ba. Consequently, GBC1.05 cathode exhibits a good cell performance of 830 mW cm −2 at 800 °C, indicating that A-site excessive Gd1.05 Ba1.05 Co2 O5+δ layered perovskite is a potential cathode material for IT-SOFCs due to its high electrochemical performance.